Sinergitas Organisasi Pokdarwis Mada Oi Tampuro dan Mahasiswa KKN Tematik Kampus Stipar Soromandi Bima Dalam Mengembangkan Potensi Wisata Oi Tampuro Desa Piong Kecamatan Sanggar - Marwan, Marwan; Abdurrahman, Abdurrahman; Najamudin, Najamudin (Majalah Ilmiah Dinamika Administrasi (MIDA), 2024)
Research synergy between the tourism village management organization (pokdarwis) oi Tampuro and thematic real work lecture (KKN) students of STIPAR Soromandi Bima campus in developing the tourism potential of Piong Village, District. The synergy of the two parties is an important key in efforts to maximize the local potential owned by Piong Village. This study uses a qualitative approach with a case study method, which is collected through interviews, observations, and documentation. The results of the study show that the synergy between pokdarwis Oi Tampuro and KKN students plays a very important role in developing tourism in Piong Village, especially in aspects of human resource development, promotion, and management of local natural and cultural potential.